Nutrient Intake of College Students Improved with Implementation of a Food Scholarship Program (P04-068-19). (13th June 2019) - Moore, Carolyn; Alexis, Torrey; Unruh, Deborah; Wang, Wanyi
Abstract: Objectives: To determine the efficacy of a new food scholarship program by assessing changes of food security status, nutrient intake, and food group servings over a 10-week period. Methods: A food scholarship program was implemented at Texas Woman's University in Houston. Students were provided twice a month fresh fruits and vegetables, dairy and meat products, as well as non-perishable foods donated by the Houston Food Bank. Baseline and 10 week data were collected. Food security was measured using the United States Department of Agriculture 6 question survey. Nutrient intake and number of food group servings were determined by analysis of 3-day food records. Paired t-tests were performed (SPSS v25) to assess changes with an alpha of 0.05 set for significance. Results: Participants ( n  = 49) were primarily female ( n  = 38, 78%) with an average age of 28 ± 8 years. Ethnic/race distribution was 49% White, 27% Asian, 20% Black, and 4% other. Students were primarily single (76%) with few children. Food security was low or very low at baseline (51%) and remained low or very low at 10 weeks (45%). Increased nutrient intake included protein (76 ± 29 to 90 ± 34 gm/d, P  = 0.001), niacin (37 ± 15 to 42 ± 15 mg NE/d, P  = 0.002), magnesium (254 ± 98 to 285 ± 106 mg/d, P  = 0.034), phosphorous (1196 ± 730 to 1235 ± 449 mg/d, P  = 0.039), and potassium (2.2 ± 0.1.9 to 2.5 ± 0.9 g/d, P  = 0.019). Overall, the number of vegetable servings increased (2.6 ± 1.8 to 3.3 ± 2.0/d, P  = 0.034). Few students (26%) were achieving the recommended dietary intake of Vitamin D (26%) or Vitamin E (60%) and sodium intake exceeded recommendations by more than 200%. Conclusions: Implementation of a food scholarship program increased nutrient intake (protein, niacin, magnesium, phosphorus, and potassium) and servings of vegetables. Nevertheless, many college students remained food insecure and several nutrients remained below recommended intake levels. Funding Sources: Houston Food Bank provided the food.